2009
DOI: 10.1177/0022034509354298
|View full text |Cite
|
Sign up to set email alerts
|

Is Zoledronate Toxic to Human Periodontal Fibroblasts?

Abstract: Exposed necrotic alveolar bone is a hallmark of bisphosphonate-related osteonecrosis of the jaw. However, it is unknown whether zoledronate causes soft-tissue damage via adverse actions toward periodontal fibroblasts. We therefore examined whether zoledronate causes a cytotoxic response in fibroblasts isolated from the gingiva and the periodontal ligament. We report that micromolar concentrations of zoledronate and serum-free conditions decreased cell activity, as measured by assays for formazan formation, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 26 publications
7
51
2
2
Order By: Relevance
“…Therefore, one may speculate that the irreversible cell damage caused by ZA on the cultured fibroblasts may interfere negatively with tissue repair processes in vivo, as described in previous studies. 1,29 It appears that the intense toxic effect caused by ZA induced rapid fibroblast apoptosis, such that subsequent laser irradiation of ZA-treated cells at specific parameter levels had no positive effects, since the apoptotic process is considered an irreversible pathway. 30 In this study, we demonstrated that LLLT can biostimulate cultured gingival fibroblasts, leading to increased cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one may speculate that the irreversible cell damage caused by ZA on the cultured fibroblasts may interfere negatively with tissue repair processes in vivo, as described in previous studies. 1,29 It appears that the intense toxic effect caused by ZA induced rapid fibroblast apoptosis, such that subsequent laser irradiation of ZA-treated cells at specific parameter levels had no positive effects, since the apoptotic process is considered an irreversible pathway. 30 In this study, we demonstrated that LLLT can biostimulate cultured gingival fibroblasts, leading to increased cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies about BRONJ are focused on bone tissue [9,10]. However, oral soft tissue is extremely important, as its rupture and breakdown is necessary for the progression of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] In addition to the effects of BPs on osteoclasts and osteoblasts, recent studies indicated that BPs, especially the highly potent nitrogen-containing BPs, can inhibit fibroblast proliferation and increase their apoptosis. [19][20][21][22] Thus, treatment with BPs may help to reduce fibrous encapsulation and enhance implant osseointegration. However, since a number of recent studies have shown that systematic administration of BPs especially by intravenous injection may be associated with a severe bone disease, osteonecrosis of the jaws (ONJ), [23][24][25] development of strategies for local BP administration may be necessary to prevent this adverse effect.…”
mentioning
confidence: 99%
“…S3). Earlier, in vitro studies indicated that the effective concentration of soluble BPs to induce significant apoptosis and suppress fibroblast proliferation is in the range of 10-100 mM, 20,22,38 but the relevant data for immobilized BPs are not available. Our results show that with a surface density of loaded alendronate of only 0.14 -0.08 mmol/cm 2 (0.046 -0.03 mg/cm 2 ) (i.e., Ti-CaPAlen0.5 substrate), a significant decrease in fibroblast proliferation was attained.…”
mentioning
confidence: 99%